1880 Miss. Rev. Code 775 - (:unkn) unknown (My University, 1880)
Ch. 77, § 2983: If any person assaults and beats another with a cowhide, whip or stick, having at the time in his possession a pistol or other deadly weapon, with intent to intimidate the person assaulted, and prevent him from defending himself, he shall on conviction be imprisoned in the penitentiary not longer than ten years.]
Keywords: COMMITTING CRIME W/ WEAPON